Kapwa Agta an awareness campaign on the rights of indigenous peoples and ancestral domain empowering the Agtas of Casiguran in raising solidarity for collective action in addressing the displacement caused by the development of APECO (RA 10083) - Dela Concepcion, Ana Sofia V.; Sicat, Jose Manuel (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Ancestral domain is rich in vast lands, sprawling forests and abundant watersheds. Many of the Philippines' natural resources thrive in these territories. Indigenous cultural communities have settled and continue to maintain the flora and fauna of their respective ancestral domain throughout the country. Since the onset of the colonial period of the Philippines, indigenous peoples have been facing problems of displacement and ownership. These problems sprout into numerous forms of human rights and violations that have been carried on to the Indigenous Peoples of the Philippines today. Many investors and developers take interest on the Ancestral Domain because of its abundance in natural resources. This causes the nationwide struggle of protecting Indigenous People's culture.

Despite the existence of laws and institutions protecting Indigenous Cultural Communities, Indigenous Culture remains as stake because of other existing laws in the Philippine constitution. These laws bypass and overlook the importance of the linkage of Ancestral Domain and Indigenous Cultural Communities.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 112-114
Keywords: Aetas (Philippine people); Indigenous Peoples; APECO; Ancestral domain